2013
DOI: 10.3758/s13428-013-0339-9
|View full text |Cite
|
Sign up to set email alerts
|

PC-PVT: A platform for psychomotor vigilance task testing, analysis, and prediction

Abstract: Using a personal computer (PC) for simple visual reaction time testing is advantageous because of the relatively low hardware cost, user familiarity, and the relative ease of software development for specific neurobehavioral testing protocols. However, general-purpose computers are not designed with the millisecond-level accuracy of operation required for such applications. Software that does not control for the various sources of delay may return reaction time values that are substantially different from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 13 publications
1
85
0
1
Order By: Relevance
“…Conveniently, this test has been recently developed and validated using a freely downloadable personal computer-based (PC) software program. 24 The PVT was conducted similar to the procedures of Khitrov et al, 24 using the downloadable software, a PC laptop (Dell Precision M6500; Dell Inc., Round Rock, TX) and optical gaming mouse (Razer Abyssus; Razer, Carlsbad, CA). The PVT was 5 minutes in duration, and subjects were asked to turn off all personal electronic devices and were not allowed to have any other persons present in the room during the test administration.…”
Section: Reaction Timementioning
confidence: 99%
See 1 more Smart Citation
“…Conveniently, this test has been recently developed and validated using a freely downloadable personal computer-based (PC) software program. 24 The PVT was conducted similar to the procedures of Khitrov et al, 24 using the downloadable software, a PC laptop (Dell Precision M6500; Dell Inc., Round Rock, TX) and optical gaming mouse (Razer Abyssus; Razer, Carlsbad, CA). The PVT was 5 minutes in duration, and subjects were asked to turn off all personal electronic devices and were not allowed to have any other persons present in the room during the test administration.…”
Section: Reaction Timementioning
confidence: 99%
“…The PVT was selected, as it is considered to be the ''gold standard'' 24 vigilance and visual RT test, and has been successfully used in nursing populations. Notably, Surani et al 16 have suggested that it may be relevant to nurses because ''professional vigilance, the art of 'watching out' is the essence of nursing'' (pg.…”
Section: Reaction Timementioning
confidence: 99%
“…The Psychomotor Vigilance Test (PVT), developed in the 1980s by Dinges and Powell (1985), is a good example of such a tool. Indeed, the PVT is currently the most popular validated reaction time (RT) test for sleep research and has been the gold standard in the field for many years (Dinges & Powell, 1985;Khitrov et al, 2014). However, the PVT is available and validated on only a very limited number of devices, including the original PVT-192 and a few computer-based versions.…”
mentioning
confidence: 99%
“…Others have used different methodology to determine the device latency between a response box and RT documented on a computer-based test (Khitrov et al, 2014). Although we could have connected an RT box to the touch screen device to determine the latency arising from software processing, we chose to evaluate the latency using a high-speed camera in order to also capture differences between individuals relating to the administration of the PVT on a touch screen device.…”
Section: Before Offsetmentioning
confidence: 99%